2020
DOI: 10.1084/jem.20201181
|View full text |Cite
|
Sign up to set email alerts
|

Measuring SARS-CoV-2 neutralizing antibody activity using pseudotyped and chimeric viruses

Abstract: The emergence of SARS-CoV-2 and the ensuing explosive epidemic of COVID-19 disease has generated a need for assays to rapidly and conveniently measure the antiviral activity of SARS-CoV-2–specific antibodies. Here, we describe a collection of approaches based on SARS-CoV-2 spike-pseudotyped, single-cycle, replication-defective human immunodeficiency virus type-1 (HIV-1), and vesicular stomatitis virus (VSV), as well as a replication-competent VSV/SARS-CoV-2 chimeric virus. While each surrogate virus exhibited … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
466
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(483 citation statements)
references
References 47 publications
17
466
0
Order By: Relevance
“…2a and Extended Data Fig. 2a ), when entry was probed using vesicular stomatitis virus (VSV) pseudoparticles carrying the SARS-CoV-2 spike protein and expressing the green fluorescent protein (GFP) 14 . However, when ACE2 and TMPRSS2 were expressed together, most of the cell lines became highly susceptible to infection, with 293T, Calu-6, HuH-6, Huh-7.5, and Caco-2 cells demonstrating considerably higher infection efficiency than Vero E6 cells.…”
Section: Resultsmentioning
confidence: 99%
“…2a and Extended Data Fig. 2a ), when entry was probed using vesicular stomatitis virus (VSV) pseudoparticles carrying the SARS-CoV-2 spike protein and expressing the green fluorescent protein (GFP) 14 . However, when ACE2 and TMPRSS2 were expressed together, most of the cell lines became highly susceptible to infection, with 293T, Calu-6, HuH-6, Huh-7.5, and Caco-2 cells demonstrating considerably higher infection efficiency than Vero E6 cells.…”
Section: Resultsmentioning
confidence: 99%
“…2). Previous studies demonstrated that the neutralizing activity of convalescent plasma measured with this method correlates quantitatively with neutralizing activity measured using an authentic SARS-CoV-2 neutralization assay (18,19). Neutralizing activity against SARS-CoV-2 WT or D614G S glycoprotein, as measured by the neutralization half-maximum inhibitory dilution (ID 50 ), was detected in 71% of patients 6 weeks after the onset of symptoms.…”
mentioning
confidence: 85%
“…Infectivity of virions was determined by titration on 293T ACE2 cells. Further details are described elsewhere 33 .…”
Section: Sars-cov-2 and Sars-cov Pseudotyped Reporter Virusesmentioning
confidence: 99%